Faktor-faktor yang Memengaruhi Motivasi Petani Padi Sawah Desa Kondamara Kecamatan Lewa Kabupaten Sumba Timur - Tamar, Adriana Dembi; Retang, Elfis Umbu Katongu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the level of motivation and factors that influence the motivation of farmers in cultivating rice fields in Kodamara Village, Lewa District, East Sumba Regency. The number of samples used in this study was 86 farmers who cultivated rice fields in Kondamara Village. Data analysis was carried out using a descriptive method, namely to describe the level of motivation of farmers in cultivating rice fields in Kondamara Village, then measuring the level of motivation using a Likert scale. To analyze the factors that influence motivation, multiple linear regression analysis was carried out. The results of the analysis explain that the level of motivation of rice farmers in Kondamara Village, Lewa District, East Sumba Regency is in the very high category with an average ERG value of 50.24. The variables of education, income and market opportunities have a significant influence on farmer motivation. The variables of age, number of dependents, experience, availability of capital institutions and farming risks do not have a significant influence on farmer motivation.